2019
DOI: 10.1017/s1355617719000286
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Wellness After Pediatric Concussion

Abstract: Objective: Concussion in children and adolescents is a prevalent problem with implications for subsequent physical, cognitive, behavioral, and psychological functioning, as well as quality of life. While these consequences warrant attention, most concussed children recover well. This study aimed to determine what pre-injury, demographic, and injury-related factors are associated with optimal outcome (“wellness”) after pediatric concussion. Method: A total of 311 children 6–18 years of age with concussion parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Additionally, a similar proportion of those with migraines had symptoms at 28 days post injury (35%) compared to the entire sample (32%; p = 0.72) ( 16 ). A different prospective study that examined sports concussions in patients ages 12–17 who presented to an emergency department did not show a higher likelihood of prolonged recovery ( 46 ). In contrast, another study examined youth ages 5–18 who presented to emergency departments across Canada and found a higher portion of the migraine group (42.6%) had symptoms at 28 days post injury, compared to 28.1% of the group without migraines ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a similar proportion of those with migraines had symptoms at 28 days post injury (35%) compared to the entire sample (32%; p = 0.72) ( 16 ). A different prospective study that examined sports concussions in patients ages 12–17 who presented to an emergency department did not show a higher likelihood of prolonged recovery ( 46 ). In contrast, another study examined youth ages 5–18 who presented to emergency departments across Canada and found a higher portion of the migraine group (42.6%) had symptoms at 28 days post injury, compared to 28.1% of the group without migraines ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is essential to appreciate that only one study was designed specifically to examine migraine as a risk factor ( 45 ). All other studies included migraine as a secondary or exploratory variable; some studies discussed their rationale for examining pre-injury migraines ( 10 , 20 , 34 37 , 41 43 , 46 ), while others did not ( 13 , 14 , 16 19 , 21 , 30 , 32 , 33 , 38 40 , 44 ). Most studies ( n = 19/25, 76%) did not find a statistically significant association between having pre-injury migraines and a prolonged recovery or worse clinical outcome following concussion, two studies had both significant and null findings, and four studies showed only significant findings.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study carried out by Beauchamp et al among children aged 6-18 years also highlighted that those who sustained sports or recreationalrelated concussions had a better quality of life and were less likely to experience persistent post-concussion symptoms and cognitive impairment. [11] Both studies suggest that these differences could be explained by particular biomechanical characteristics (velocity of impact, distribution of the forces, location and speed) which potentially differ between motor vehicle collision, bicycle accidents or falls and sports injury. As recently shown, brain tissue stresses and strains are related to the impact force of the injury [31].…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…There are numerous available studies regarding mild TBI pathophysiology [7], diagnosis [5,8], treatments [5,9,10], predictors of wellness [11,12] and symptom evolution [13]. Since about 24% of mild TBI patients remain significantly impaired by persistent symptoms such as headaches, dizziness and fatigue at 3-month follow-up [14], many studies have analyzed the impact of mechanisms of injury on persistent post-concussion symptoms while evaluating other risk factors [11,[15][16][17][18]. However, sport as the mechanism of injury has an impact on the recovery and return to normal activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation